Influence of different levels of iron and molybdenum on nitrogen fixation and phosphate solubilization in aerobic rice - Sambudin, Siti Nur` Ain (2019)
Growth and yield of aerobic rice (Oryza sativa L.) is affected by macro and micro-elements in soil. Biological nitrogen fixation (BNF) and phosphate solubilization by microorganisms are alternatives to reduce the use of high chemical fertilizers in rice cultivation. Iron (Fe) and molybdenum (Mo) are part of nitrogenase enzyme and abundance or shortage of these elements may affect N₂-fixation as well as phosphate solubilization. The following studies aimed to determine i) the effect of different concentrations of Fe and Mo on growth of N₂-fixing bacteria (NFB) and P-solubilizing bacteria (PSB), ii) the effect of inoculation with NFB and PSB on growth of rice applied with different concentrations of Fe and Mo and iii) the effect of microbial inoculation with combined Fe and Mo on growth and nutrient uptake of aerobic rice. Studies were conducted in the laboratory and glasshouse conditions. Four concentrations of Fe (0, 2, 10, 50 ppm) and Mo (0, 0.05, 5, 10 ppm) were evaluated on growth of two Bacillus sp. strains in modified nitrogen free broth and nutrient broth. Bacterial enumeration was done at the end of incubation. In the following study, the same concentrations of Fe and Mo were applied to aerobic rice seedlings in sand culture. Seven days old seedling was inoculated with NFB and PSB each as single and combined inoculum and grown for 40 days. Modified Yoshida nutrient solution was applied to each pot twice per week. The best concentrations of iron and molybdenum from previous experiment were selected and evaluated on aerobic rice plant as a combined micronutrient and inoculated with a single and a combined NFB and PSB for 60 days. Inoculum and nutrient solution applied was similar to previous experiment. Results showed that different concentrations of Fe and Mo significantly affected NFB and PSB and P-solubilizing activity. Application of different concentrations of Fe and Mo and inoculated with NFB and PSB as single or combination significantly affected plant biomass, plant height, leaf chlorophyll content, leaf area index, root development, N and P content, and nutrient uptake of aerobic rice. Combination of Fe and Mo inoculated with single and combined NFB and PSB significantly affected plant biomass, plant height, leaf chlorophyll content, leaf area index, root development, N and P content, nutrient uptake and total bacterial population in rhizosphere and endophyte. In conclusion, application 50 ppm of Fe and 10 ppm of Mo along with combined NFB and PSB enhanced plant growth and uptakes of aerobic rice.